MODERASI BERAGAMA: STUDI KOMPARASI PANDANGAN AL-AZHAR DAN KEMENTRIAN AGAMA REPUBLIK INDONESIA - Kurniati; Abd. Rahman; andi, fadhil (Sanjiwani: Jurnal Filsafat, 2023)
Moderation in religion is often seen as an attitude of not having solid principles in carrying out religious norms, resulting in extreme and liberal traits because they do not understand the concept of balance in religion. So this article aims to find out the nature and reality of moderation in religion so as not to lead to deviant traits. The method in this study leads to qualitative literature. The Indonesian Ministry of Religion and al-Azhar Egypt are two institutions that are keen to spread this understanding, so the efforts made by these two agencies have different concepts and values from one another but with the same goal of grounding moderation in Islam.